Catalytic Recovery of Elemental Sulfur Using a Novel Catalytic Membrane Reactor at Room Temperature with a Layer of Dispersed Mo-Co/γ-Al2O3 Catalyst: Reaction Kinetics and Mass Transfer Study - Chen, Xiao Yuan; Kaliaguine, Serge; Rodrigue, Denis (Journal of Membrane and Separation Technology, 2017)
The mass transfer rate of catalytic recovery of sulfur is investigated, enters through the catalyst-membrane interface (layer), accompanied by pseudo-first order irreversible reaction. Reaction kinetics is measured considering the system as a homogeneous system due to the consideration of mixed flow patterns of the reacting fluids, though the catalysis is a heterogeneous one. The multi-reactant mass transfer behaviour of the catalytic membrane reactor (CMR) is also studied on the basis of Maxwell-Stefan theory to understand the diffusion of reactants inside the membrane reactor. The mass transport behaviour and the performance of the fabricated CMR are strongly influenced by the reaction conditions, such as, reaction equilibrium constant (Keq) and membrane properties, namely, membrane area and reactor volume. An intermediate value with asymptotic nature of Keq as a function of time indicates appreciable performance of the catalytic membrane. On the other hand, the minimum value of kij indicates a negligible effect on mass transfer over the reactor performance.